2020
DOI: 10.11604/pamj.2020.36.94.23757
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous bilateral anterior shoulder dislocation as a result of minimal trauma

Abstract: Simultaneous bilateral anterior shoulder dislocation is rare, it often occurs after high energy trauma, we report a case of a 43-years-old male presented with bilateral anterior shoulder dislocation when he tries to stand up from the floor, shoulders in extension, abduction and external rotation. A closed reduction was performed without complications, and one month later the right shoulder was stabilized by open Laterjet technique. The evolution was favorable for both shoulders with no pain, recuperation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…Although bilateral shoulder dislocation is most often posterior, there are a few cases of bilateral anterior shoulder dislocation reported in the literature. They are the result of high-energy trauma, most often during high-speed sports accidents [ 1 ]. In young patients, like in the present case, the main complication of anterior shoulder dislocation is the instability of the shoulder; a prospective cohort study reported that 55.7% of young patients developed a recurrence of shoulder instability within two years [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although bilateral shoulder dislocation is most often posterior, there are a few cases of bilateral anterior shoulder dislocation reported in the literature. They are the result of high-energy trauma, most often during high-speed sports accidents [ 1 ]. In young patients, like in the present case, the main complication of anterior shoulder dislocation is the instability of the shoulder; a prospective cohort study reported that 55.7% of young patients developed a recurrence of shoulder instability within two years [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent shoulder dislocation is a debilitating condition that significantly affects the quality of life of affected individuals. Bilateral involvement is rare but can lead to severe functional limitations [ 1 ]. While conservative management is typically attempted initially, surgical intervention may be required in cases of recurrent instability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations